Emotions and human mobility ethnographies of movement - Svašek, Maruška (Routledge, 2012)
"This book provides insights into the emotional dimensions of human mobility. Drawing on findings and theoretical discussions in anthropology, sociology, cultural studies, philosophy, linguistics, migration studies, human geography and political science, the authors offer interdisciplinary perspectives on a high topical debate, asking how 'emotions' can be conceptualised as a tool to explore human mobility. 'Emotions and Human Mobility' investigates how emotional processes are shaped by migration, and vice versa. To what extent are people's feelings about migration influenced by structural possibilities and constraints such as immigration policies or economic inequality? How do migrants interact emotionally with the people they meet in the receiving countries, and how do they attach to new surroundings? How do they interact with 'the locals', with migrants from other countries, and with migrants from their own homeland? How do they stay in touch with absent kin? The volume focuses on specific cases of migration within Europe, intercontinental mobility, and diasporic dynamics. Critically engaging with the affective turn in the study of migration, 'Emotions and Human Mobility' will be highly relevant to scholars involved in current theoretical debates on human mobility. Providing grounded ethnographic case studies that show how theory arises from concrete historical cases, the book is also highly accessible to students of courses on globalisation, migration, transnationalism and emotion"--P. [iii]